O impacto de restrições monetárias sobre análises de acessibilidade e equidade nos transportes - Santos, Daniel Herszenhut Meirelles (2021)
Transport equity analyses are often informed by accessibility estimates based solely on travel time impedance, ignoring other elements that might hinder access to activities, such as the monetary cost of a trip. This thesis examines how and to what extent simultaneously incorporating travel time and monetary costs constraints into accessibility measures may impact transport equity assessment. The job accessibility by transit in the city of Rio de Janeiro, Brazil, is calculated using cumulative opportunity measures under distinct combinations of temporal and monetary thresholds. The inequality levels of each one of these scenarios are then calculated and compared. The results suggest that the most common research practice of disregarding monetary costs tends to overestimate accessibility levels. However, stricter monetary constraints do not necessarily result in less equitable scenarios. How accessibility inequality is affected by monetary costs is highly dependent on what combinations of temporal and monetary cut-offs are considered in the analysis. This is the result of a complex interaction between fare policies, the spatial organisation and operational characteristics of transit systems, and the spatial co-distribution of jobs and residential locations. The results also suggest that in Rio’s case the rail is a vital mode to combat transport inequalities, and that offering discounts between the rail and more widely distributed transit modes could increase the accessibility levels of low-income individuals without requiring adjustments to physical infrastructure and services’ timetables.